2018
DOI: 10.1111/1750-3841.14058
|View full text |Cite
|
Sign up to set email alerts
|

Green Tea Polyphenols Modulate Colonic Microbiota Diversity and Lipid Metabolism in High‐Fat Diet Treated HFA Mice

Abstract: A high fat diet significantly impacted gut microbiota composition and lipid metabolism in human flora-associated mice, which were largely ameliorated by tea polyphenol (TP). Therefore, TPs may be effectively used in controlling or treating obesity, hyperlipidemia and other related metabolic diseases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
76
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 111 publications
(82 citation statements)
references
References 60 publications
6
76
0
Order By: Relevance
“…34 An increased Firmicutes/Bacteroidetes ratio (F/B) was observed in LMG and LLG of cecum, whereas the reverse results were obtained in colon. Wang et al 33 reported that the increased F/B ratio induced by tea polyphenol may have benefits for weight loss and in the treatment of related metabolic diseases. This indicated that the consumption of limonene and linalool might have this healthy function.…”
Section: Analysis Of Intestinal Microfloramentioning
confidence: 99%
“…34 An increased Firmicutes/Bacteroidetes ratio (F/B) was observed in LMG and LLG of cecum, whereas the reverse results were obtained in colon. Wang et al 33 reported that the increased F/B ratio induced by tea polyphenol may have benefits for weight loss and in the treatment of related metabolic diseases. This indicated that the consumption of limonene and linalool might have this healthy function.…”
Section: Analysis Of Intestinal Microfloramentioning
confidence: 99%
“…Therefore, from the volunteers under the experiment used (BT and GT) as AH, that were considered the main drinking of them for their beneficial. While other T types did not show benefits for DS, but showed some effects and tired of DS [13][14][15][16][17][18] . That revealed the equivalent dose of T bags had a multiplier effect on DS, as it might be enough to more than one cup might be was enough to (3-4) T cups.…”
Section: Methodsmentioning
confidence: 99%
“…The results indicated the importance of TP to modify performance in DS through support and help GM. BWTE were arranged according to the support effect on GM as (BT, GT, WT, RT and MT) respectively [13][14][15][16][17][18] . Table and graph 3 revealed prevalence of DS-PF during experiment internally in-vivo, through the experiment found the DS-PF ranging from (25-50%) and this created failure of DS functions, killed GM and were consequent to affect digestion and absorption.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the transmission route, the metabolism mechanism in the fetus and the effects of fetal exposure to bioactive diets need be further studied. Other bioactive epigenetic diets such as green tea polyphenols have been reported to improve HFD-induced metabolic disorders partially through regulation of gut microbial diversity (Wang et al, 2018), although the effects of maternal green tea polyphenols on the fetus microbiota remains unclear.…”
Section: Maternal Diet Epigenetics and Gut Microbiome In Developmentmentioning
confidence: 99%